Peningkatan Pemahaman Konsep Perkalian dan Pembagian Pecahan melalui Pendekatan Matematika Realistik Berbantuan Alat Peraga Papan Ajaib - Lia Fitriani Trengganis; M Maulana; Riana Irawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Students' lack of conceptual understanding of fraction content is the driving force behind this research, which seeks to address this issue through instruction that can improve students' conceptual understanding. One of them is the use of magic board props combined with a realistic mathematical approach. With the use of realistic mathematical procedures including magic board props, this study sought to ascertain the extent to which students understand multiplication and division of fractions, as well as provide an explanation for this progress. Using nonequivalent control group research and quantitative research techniques, this research uses a quasi-experimental design. Participants in this research were fifth grade students at SDN Cimalaka III and SDN Citimun II. This assessment tool measures the subject's ability to grasp abstract ideas. On average, students' concept understanding skills improved by 72.21% and 66.76% respectively when taught mathematics using realistic mathematics methods compared to traditional approaches, according to the research. Fifth grade students' conceptual understanding can be improved with the use of teaching aids and realistic mathematics learning approaches. On average, the experimental group had an N-Gain of 0.5674, while the control group had 0.4184. This shows that compared with the control group, students in the experimental group gained 0.149 greater conceptual knowledge. Simply put, experimental group students who were taught mathematical concepts using a realistic approach using a magic board had a better understanding of the material than the control group who were taught using a more traditional approach.